(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article studies the role and importance of fairy tales and stories in the development of speech activity of primary school students. It is argued that fairy tales and stories are an important tool for increasing children’s vocabulary, mastering grammatical structures, developing thinking skills, expanding creative imagination, and forming speech communication skills. The article analyzes the pedagogical possibilities and effective methods of using fairy tales and stories in the educational process.